HOLIDAY VOCABULARY IN MACEDONIAN TRADITIONAL CULTURE (Slavic Studies, 2025)
The subject of our interest are the chrononyms that reflect how people perceive each of the seven days of the week, referring also to the broader ritual-customary context with which a specific day is associated. Usually they represent noun idioms where the name of the day is the key component, while the attribute refers to some Christian holiday, i.e. to elements of ritual practice, to beliefs associated with that day, based on the traditional perception or interpretation of the specific holiday as part of the folk religion. Chrononyms are mainly related to the role of each day of the week in the traditional calendar, to their meaning in Macedonian ritual and magical practice, which can be same or different from the meaning in other South Slavic cultures. The names and traditional perceptions of the days in Macedonian traditional culture have been influenced by several factors, such as their associations to certain saints, to mythological creatures, as well as to beliefs in “good”, “lucky” versus “bad”, “unlucky” days. The last aspect is related to life experiences, taking into account that one day can be “good” for one type of activity, and “bad” for another, which is part of another segment of life, for e.g. agricultural activity, etc.
Keywords: days of the week; traditional calendar; customs; ritual actions; beliefs